Chromatography-mass spectrometric study of the chemical composition of Myrtus communis L. leaf essential oil - Matsehorova, O. Ye.; Odyntsova, V. M.; Мацегорова, О. Є.; Одинцова, Віра Миколаївна (Запорізький державний медико-фармацевтичний університет, 2025)
The aim of the work is to conduct a chromatography-mass spectrometric analysis of the chemical composition of Myrtus communis L. leaf essential oil. Materials and methods. The object of the study is the essential oil of Myrtus communis, cultivated at the Department of Pharmacognosy, Pharmacology and Botany of Zaporizhzhia State Medical and Pharmaceutical University, and obtained through hydrodistillation. Qualitative and quantitative determination of the essential oil components was carried out using the chromatography-mass spectrometric method on a high-performance gas chromatograph “Agilent 7890B GC System” (Agilent, SantaClara, CA, USA) with a mass spectrometric detector “Agilent 5977 BGC/MSD” (Agilent, SantaClara, CA, USA) and a DB-5ms chromatographic column (30 m × 250 μm × 0.25 μm). The component identification was performed using the NIST14 mass spectral library. Results. Chromatography-mass spectrometric analysis revealed the presence of 42 key volatile compounds in Myrtus communis leaf essential oil, three of which were in isomeric forms. The five major components were myrtenyl acetate (24.12 %), linalool (16.73 %), cyclofenchene (10.37 %), o-xylene (7.85 %) and myrtenol (4.35 %). Terpenes were identified as the dominant group in Myrtus communis leaves, comprising 72.04 %. Мета роботи – хромато-мас-спектроскопічне дослідження хімічного складу ефірної олії листя Myrtus communis L. Матеріали і методи. Об’єкт дослідження – ефірна олія мирту звичайного, що вирощений на кафедрі фармакогнозії, фармакології та ботаніки Запорізького державного медико-фармацевтичного університету. Ефірна олія одержана методом гідродистиляції. Якісне та кількісне визначення компонентів ефірної олії здійснили з використанням хромато-мас-спектрометричного методу на високоефективному газовому хроматографі Agilent 7890B GC System (Agilent, SantaClara, CA, USA) з мас-спектрометричним детектором Agilent 5977 BGC/MSD (Agilent, SantaClara, CA, USA) та хроматографічною колонкою DB-5ms (30 м × 250 мкм × 0,25 мкм). Для ідентифікації компонентів використано бібліотеку мас-спектрів NIST14. Результати. У результаті хромато-мас-спектрометричного дослідження виявлено 42 характерні компоненти летких сполук (3 із них – в ізомерному стані) в ефірній олії листя мирту звичайного з найбільшим вмістом таких п’яти компонентів: миртенілацетат (24,12 %), ліналоол (16,73 %), циклофенчен (10,37 %), О-ксилол (7,85 %) та миртенол (4,35 %). Встановили, що основна складова листя мирту звичайного – терпени з кількісним вмістом 72,04 %.
Хромато-мас-спектроскопічне дослідження хімічного складу ефірної олії листя Myrtus communis L.
Keywords: Myrtus communis; volatile organic compounds; chromatography-mass spectrometry; мирт звичайний; леткі органічні сполуки; хромато-мас-спектрометрія